Effect of microwave irradiation direction on tensile properties of granite Brazilian disc test - Wang, Yun-Long; Yang, Ben-Gao; Zhang, Dong; Zhou, Xue-Min; Xie, Jing (Thermal science, 2025)
Investigating the tensile properties of rock under varying microwave irradiation directions is essential for understanding the mechanical behavior of microwave-induced rock breaking. A continuous-discrete method is employed to analyze the tensile properties of granite disc samples under three different microwave irradiation directions. The results indicate the variable tensile properties of granite Brazilian disc under different microwave irradiation directions.